(untitled) (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of premenstrual syndrome and menstrual disorders among female students at Thai Nguyen University of Medicine and Pharmacy; and to assess factors associated with these conditions. Subjects and methods: A cross-sectional descriptive study was conducted on 587 female students from January to May 2026. Participants were selected using stratified sampling by academic year. Data were collected using self-administered questionnaires, including the WHO menstrual disorder assessment questionnaire, the PSST, the PSS, and the IPAQ-SF. Results: The prevalence of menstrual disorders was 84.5%, premenstrual syndrome was 32.4%, and premenstrual dysphoric disorder was 3.9%. Most premenstrual syndrome symptoms were mild to moderate; common moderate-to-severe symptoms included fatigue/lack of energy (56.6%) and increased need for sleep (58.8%). The prevalence of premenstrual syndrome was significantly higher among students with high stress levels (71.4%) compared with those with moderate (30.3%) and low stress levels (8.7%) (p < 0.001). Other factors, including age, ethnicity, body mass index, age at menarche, and physical activity level, showed no significant association (p > 0.05). Conclusions: The prevalence of menstrual disorders and premenstrual syndrome among female students remained high. Stress level was significantly associated with premenstrual syndrome. Stress management, psychological counseling, and reproductive health education should be strengthened to improve female students’ physical and mental well-being.